SOIL FERTILITY STATUS OF ALLUVIAL ON CONVENTIONAL RUBBER PLANTATION AT PANCAROBA VILLAGE DISTRICT SUNGAI AMBAWANG KUBU RAYA REGENCY - David .; Urai Suci Y.V.I; Rinto Manurung (Jurnal Sains Pertanian Equator, 2019)
Plant production is inseparable from the factor of soil fertility. As a living organism, plants need nutrients to carry out their growth. High soil fertility will make optimal plant growth and production. Soil fertility is directly related to plant growth so that an assessment of soil fertility status is absolutely necessary. Management of rubber plantations is expected to be done efficiently so that the level of soil fertility is known. This study aims to determine the status of soil fertility in the research location in the community rubber plantation in Pancaroba Village, Sungai Ambawang District, Kubu Raya Regency. The study was conducted by survey method and interviews with farmers to get an overview of the research location. The next step is to take soil samples at a depth of 0-30 cm and 30-60 cm in productive and unproductive rubber plantations. Based on observations of soil pH at the research location is classified as acid. C-Organic at the research location is high to very high. Nitrogen (N) levels of total soil at the study site are classified as moderate to very high. Phosphorus (P) levels of soil available at the study site are relatively low. Potassium (K) levels can be exchanged soils at the study sites are relatively low. Ca-dd at the study site was classified as very low while Mg-dd was classified as low. The Cation Exchange Capacity (CEC) of Soil at the research location is low to moderate, while the Saturation of Bases is very low and Al Saturation is very high. The texture at the study site is included in the clay texture class. Key word:Nutrient status, Rubber plant, Soiled fertility.